Structural and magnetic ordering in Pr0.65(CaySr1-y)0.35MnO3: "quantum critical point" versus phase segregation scenarios - Blake, G; Chapon, L; Radaelli, P; Argyriou, D; Gutmann, M; Mitchell, J (2002)
The phase diagram of Pr0.65(CaySr1-y)0.35MnO3, 0.6 <= y <= 0.8, has been determined by neutron diffraction, magnetization and electrical conductivity measurements in order to investigate the nature of the transition between ferromagnetic metallic and charge-ordered insulating states near y=0.75. Two possible scenarios for this transition have been proposed: a "quantum critical point"-like feature, near which an associated charge-disordered paramagnetic phase is present, or a phase coexistence region. We demonstrate that the latter case is true, phase segregation occurring on a mesoscopic/macroscopic length-scale (several hundred Angstroms to several microns). Our results show that no significant amount of the charge-disordered paramagnetic phase is present at low temperatures. Our data also indicate that the charge-ordered insulator to ferromagnetic metal phase boundary is temperature as well as composition-dependent.